2014
DOI: 10.1002/ijc.28862
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA methylation analysis of breast cancer reveals the impact of immune signaling in radiation therapy

Abstract: Radiotherapy (RT) is a central treatment modality for breast cancer patients. The purpose of our study was to investigate the DNA methylation changes in tumors following RT, and to identify epigenetic markers predicting treatment outcome. Paired biopsies from patients with inoperable breast cancer were collected both before irradiation (n = 20) and after receiving 10–24 Gray (Gy) (n = 19). DNA methylation analysis was performed by using Illumina Infinium 27K arrays. Fourteen genes were selected for technical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…The synergistic tumor inhibition of RT combined with immunotherapy is attributed to the well-defined radiation-associated tumor priming function (abscopal effect) 40 , 41 which has been well-evidenced by induced cell surface epitopes processed and presented in radiation-treated tumors 7 , enhanced diversity of the T-cell receptor repertoire of intratumoral T cells 42 , synergic potentiation in improving immune repertoire 43 , 44 , and inhibited metastasis by RT with immunotherapy 45 . However, such radiation-associated anti-tumor immune response is rarely detected in clinic 46 , implicating a possibility that radiation-induced immunosuppressive factors may compromise the anti-tumor immune regulation induced by radiation-associated tumor immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic tumor inhibition of RT combined with immunotherapy is attributed to the well-defined radiation-associated tumor priming function (abscopal effect) 40 , 41 which has been well-evidenced by induced cell surface epitopes processed and presented in radiation-treated tumors 7 , enhanced diversity of the T-cell receptor repertoire of intratumoral T cells 42 , synergic potentiation in improving immune repertoire 43 , 44 , and inhibited metastasis by RT with immunotherapy 45 . However, such radiation-associated anti-tumor immune response is rarely detected in clinic 46 , implicating a possibility that radiation-induced immunosuppressive factors may compromise the anti-tumor immune regulation induced by radiation-associated tumor immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, previous studies on different solid cancers have highlighted the role of methylation deregulation in immune cell compartment as potentially involved in cancer progression [41][42][43]. More precisely, a recent study of paired breast cancer samples (before and after radiotherapy) showed that the most differently methylated pathways were linked to the immune system [44]. In the same line, the crosstalk between immune system and cancer progression has also been highlighted in glioblastoma by integrating multi-omic data showing that immune/inflammatory responses are among the most important processes associated with prognosis [45].…”
Section: Discussionmentioning
confidence: 95%
“…However the epigenetic alterations induced by RT have been left out even though these modifications can potentially lead to the change in transcriptional activity [35]. Halvorsen et al have demonstrated that DNA methylation levels of genes in the immune system pathways are significantly altered after irradiation in breast cancer [36]. In another melanoma mouse model, Victor et al have demonstrated that radiation diversifies the T cell receptor (TCR) repertoire of TILs [14].…”
Section: Potential Mechanisms Of Radiotherapy Combined With Immunothementioning
confidence: 98%